Performance of classification criteria for Behcet's disease in an Egyptian cohort - Mohamed Ahmed Hussein; Mona I Ellawindi; Gaafar Ragab (Indian Journal of Rheumatology)
Background: The revised Japanese criteria, the International study group (ISG), the International criteria for Behcet's disease (ICBD) 2006, and the revised ICBD 2010 are frequently used for the classification of Behcet's Disease (BD). In this study we evaluated the performance of these criteria sets in Egyptians. Methods: A total of of 461 Egyptian patients over 5 years were studied. It included 256 patients classified as BD based on expert opinion and 205 patients with other autoimmune and/or autoinflammatory diseases with symptoms similar to BD. Performance of the revised Japanese criteria, ISG, ICBD 2006, and the revised ICBD 2010 was evaluated evaluated in terms of sensitivity, specificity, negative predictive value (NPV), negative likelihood ratio (NLR), positive predictive value (PPV), positive likelihood ratio (PLR), diagnostic odd ratio (DOR), and Youden's index (YI). Results: ICBD 2010 carried the highest sensitivity (98.83%), NPV (98.48%), DOR (1645), and YI (0.94) with lowest NLR (0.01). On the other hand, ICBD 2006 and ISG were very specific (99.51%, 99.41%, respectively) with PPV (99.49%, 99.40%) and PLR (155.35, 126.33), respectively. Conclusions: ICBD 2010 is a very good criteria set to be used in Egyptian BD patients based on its very high sensitivity, accepted specificity, and power of discrimination that enables early patients classification, management, and prognosis.